Histopathological study of pruritic papular eruptions in HIV-infected patients in relationship with CD4, CD8 counts - Annam Vamseedhar; Yelikar B; Inamadar Arun; Palit Aparna (Wolters Kluwer Medknow Publications, 2009)
Background: Pruritic papular eruptions (PPE) are common cutaneous manifestations in HIV-infected patients. Their frequencies, patterns and associated factors vary from region to region. There is no clear consensus on the etiology of PPE, the exact spectrum of the condition, the pathologic findings, or treatment. The present study is aimed at documenting the histopathological patterns of PPE, and their relation with CD4, CD8 counts in HIV-infected patients. Materials and Methods: The present study lasted for 12 months (September 2005 to August 2006). After informed consent, data on skin disorders, HIV status, CD4 and CD8 counts were obtained by physical examination and laboratory methods. Results: Of the 36 HIV-infected patients with clinical diagnosis of PPE, the most common histopathological patterns were prurigo simplex and eosinophilic folliculitis. The mean CD4 count of PPE was 186.49 cells/mm 3 with mean CD8 count of 619.60 cells/ mm 3 , and the CD4:CD8 ratio was 0.32. Patients with prurigo simplex had significantly lower mean CD4 counts (50.36 ± 30.67 cells/cmm 3 , P < 0.001) while in eosinophilic folliculitis, the mean CD8 counts were higher (1239.77 ± 402.30 cells/cmm 3 ). Conclusion: We conclude that histopathology helps in specifying the pattern of PPE and also indicates underlying immunosuppression and can be a marker of advanced HIV infection. Thus, correlation between the histopathology and immunology findings helps to know the disease process.